A Study on Online Learning Management System: Implementation of Edmodo-Based Blended English Learning Method - Ratna Yunita (Southeast Asian Journal of Islamic Education Management, 2020)
Industrial Revolution 4.0 makes rapid changes in every aspect of a human’s life. One of them is the teaching and learning English which has been affected by technology. It is supported by the fact that English is the number one language used globally. Therefore, Education 4.0 emerges in facing Industrial Revolution 4.0 to increase the education level. By this, it is expected that higher education becomes more reachable than before and a tendency which leads to more international standardized higher education institutions. In these rapid changes, there are two challenges faced by students in higher education institutions: English proficiency and culture transition. Thus, the State Islamic Institute of Ponorogo, as one of developing State Islamic Institutes in Indonesia starts to implement a blended learning system in every course as the solution. The lecturers use a variety of learning management system, including Edmodo. This study used quantitative and qualitative analysis on assessing the effectiveness of Edmodo implementation from the students’ point of view as well as determining the progress, learning engagement, as well as the students’ performance overall. The results showed that Edmodo facilitates student-centered and anytime-anywhere learning. It was also found that it makes the English course administration easier. Moreover, students asked in this study had a favorable opinion toward learning English via Edmodo. However, some disadvantages English and technical problems of using Edmodo in teaching and learning were also discussed in this study.